The Effectiveness of Reflection Learning Method to Increase the First Grade Students’ Writing Skill of SMA Negeri 2 Sungguminasa Gowa Regency - Musdalifah, Musdalifah (Majesty Journal, 2019)
This study aimed to determine the effectiveness of the reflection learning method in improving the writing skill of first-grade students at SMA Negeri 2 Sungguminasa, Gowa Regency, particularly in writing recount texts. The study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 33 students of class X. The instrument used was a writing test administered at the end of each cycle to assess three aspects of writing: content, organization, and generic structure. The findings showed a consistent improvement in students’ writing performance from Cycle I to Cycle II. In content, the mean score increased from 5.37 to 7.53, representing a 40.22% improvement. In organization, the mean score rose from 5.47 to 8.21, with a 50.09% improvement. In generic structure, the mean score improved from 5.36 to 8.38, indicating a 51.49% improvement. Overall, the students’ writing mean score increased from 5.40 in Cycle I to 7.95 in Cycle II, with a significant improvement of 47.27%. These findings indicate that the reflection learning method was effective in improving students’ writing skill, especially in developing content, organization, and generic structure in recount text writing.